Semitransparent quantum dot electroluminescent device and preparation method thereof

By using a composite layer of aluminum and alumina as the cathode injection layer in semi-transparent quantum dot electroluminescent devices, the performance problems brought about by traditional ITO electrodes and Ag electrodes are solved, and higher transparency and light transmittance are achieved, improving the performance problems of the traditional ITO electrodes and Ag electrodes. The overall performance and stability of the device are achieved.

CN119212422APending Publication Date: 2024-12-27NORTH CHINA ELECTRIC POWER UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411229083.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Preparation of ITO electrodes by conventional magnetron sputtering will cause In or Sn penetration, weakening device performance, and the injection barrier between the Ag electrode and the electron transport layer will affect device performance.

Method used

A composite layer of aluminum and alumina is used as the cathode injection layer, and prepared by vacuum evaporation method to form an Al/Al2O3 layer of a specific thickness, adjust the transparency of the device and carrier injection, and eliminate the electron transport layer and the semi-transparent electrode. barrier.

Benefits of technology

The transparency and light transmittance of semi-transparent quantum dot electroluminescent devices are improved, the carrier injection barrier is reduced, and the overall performance and air stability of the device are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119212422A_ABST
    Figure CN119212422A_ABST
Patent Text Reader

Abstract

The invention discloses a semitransparent quantum dot electroluminescent device and a preparation method thereof, and belongs to the technical field of quantum dot electroluminescent devices. According to the semitransparent quantum dot electroluminescent device, a cathode injection layer is arranged between an electron transmission layer and an Ag cathode layer, the cathode injection layer is an Al / Al2O3 layer with a proper thickness, and the layer can adjust the overall transparency of the semitransparent quantum dot electroluminescent device, so that the display effect of the device is effectively improved, and the overall light permeability of the device is improved; meanwhile, the work function of Al is lower than that of the electron transport layer, so that the injection barrier between the electron transport layer and the semitransparent electrode is eliminated, the carrier injection of the device is improved, and the overall performance of the device is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of quantum dot electroluminescent devices, and in particular relates to a semi-transparent quantum dot electroluminescent device and a preparation method thereof. Background Art

[0002] In today's era of rapid technological development, the development of the Internet of Things is obvious to all, and all kinds of objects can be connected to each other through adaptive software. In the future, every piece of glass such as windows and mirrors may become a carrier of future display technology to enrich life. Therefore, transparent / translucent display technology will develop more rapidly. Inorganic quantum dot electroluminescent devices have attracted much attention due to their excellent environmental stability and solution processing. The light-emitting diode devices made of them can achieve narrow emission half-wave peaks (<20nm) in the red, blue and green bands through the color conversion process, and the color gamut range exceeds 120% NTSC. It is regarded as one of the most promising display technologies for the next generation. With the advancement and development of science and technology, the application demand for translucent electroluminescent devices in life is becoming more and more urgent, such as augmented reality, virtual reality head-mounted displays, window displays, wearable medical devices, instrument displays, etc.

[0003] To meet the growing demand, highly efficient and highly transparent semi-transparent electroluminescent devices are needed. The preparation of transparent top electrodes is particularly important in the design and preparation of semi-transparent electroluminescent devices, which directly affects the transparency, conductivity and charge injection characteristics of the device. Semi-transparent electrodes that improve conductivity while ensuring electrode transparency and reduce the charge injection barrier are required for semi-transparent electroluminescent devices. Traditional magnetron sputtering to prepare ITO electrodes will allow In or Sn in ITO to penetrate into the lower layer during the sputtering process, thereby weakening the overall performance of the device.

[0004] Researchers are constantly exploring new transparent conductive materials, such as carbon nanotubes, graphene, silver nanowires, thin film metals and conductive polymers, to replace traditional ITO electrodes. These new materials not only have excellent conductivity and transparency, but also have better flexibility and stability, which makes it possible to prepare high-performance transparent QLEDs. On the other hand, using a thin evaporated metal electrode as the top electrode is an effective strategy. The metal electrode not only provides the necessary charge injection, but also can achieve a certain degree of transparency by controlling its thickness, thus meeting the needs of transparent display. However, there is a potential barrier for injection between the Ag electrode and the electron transport layer. This barrier hinders the injection of electrons during the process of electrons being transferred from the cathode to the electron transport layer, thereby affecting the overall performance of the device. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a semi-transparent quantum dot electroluminescent device and a preparation method thereof, while overcoming the adverse effects of traditional magnetron sputtering in preparing ITO electrodes, reducing the injection barrier between the Ag cathode and the electron transport layer, thereby providing a semi-transparent quantum dot electroluminescent device and a preparation method thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A semi-transparent quantum dot electroluminescent device comprises a glass substrate, an ITO layer, a hole transport layer, a quantum dot layer, an electron transport layer, a cathode injection layer and an Ag cathode layer arranged in sequence from bottom to top;

[0008] The cathode injection layer is a composite layer of aluminum and aluminum oxide, with the aluminum oxide being on the upper side of the aluminum.

[0009] A further improvement of the present invention is:

[0010] Preferably, the hole transport layer is any one or more of TFB, PEDOT:PSS and TCTA.

[0011] Preferably, the quantum dot layer is cadmium selenide colloid.

[0012] Preferably, the electron transport layer is any one of ZnO, ZnMgO, ZnAlO and ZnZrO.

[0013] Preferably, the cathode injection layer has a thickness of 1-4 nm.

[0014] Preferably, the thickness of the hole introduction layer is 30-45 nm; the thickness of the quantum dot layer is 25-30 nm.

[0015] Preferably, the thickness of the electron transport layer is 25-30 nm, and the thickness of the Ag cathode layer is 18-20 nm.

[0016] A method for preparing the above-mentioned semi-transparent quantum dot electroluminescent device comprises the following steps:

[0017] S1, sequentially preparing a hole transport layer, a quantum dot layer and an electron transport layer on the ITO layer;

[0018] S2, preparing a cathode injection layer on the electron transport layer by vacuum evaporation;

[0019] S3, depositing a Ag cathode layer on the cathode injection layer.

[0020] Preferably, in S2, the process of preparing the cathode injection layer by vacuum evaporation is:

[0021] A substrate including a glass substrate, an ITO layer, a hole transport layer, a quantum dot layer and an electron transport layer is placed in an evaporation chamber, a mask is placed on the electron transport layer, Al particles are placed in an evaporation boat, vacuum is evacuated and heated for evaporation, an Al layer is evaporated on the electron transport layer as a cathode injection layer, and the evaporation is stopped after the evaporation reaches a set thickness.

[0022] Preferably, during the vacuum evaporation process, the vacuum degree is 1×10 -4 Pa, and the evaporation rate is 0.1 Å / s.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention discloses a semi-transparent quantum dot electroluminescent device, in which an Al / Al2O3 layer of a specific thickness is set between an electron transport layer and a semi-transparent Ag cathode, and the layer has the function of adjusting the overall transparency of the semi-transparent quantum dot electroluminescent device, which can effectively improve the display effect of the device and enhance the overall light transmittance of the device. At the same time, since the work function of Al / Al2O3 is lower than the Fermi level of the electron transport layer used, it can form an ohmic basis, thereby eliminating the potential barrier between the electron transport layer and the semi-transparent electrode during carrier injection, and then can adjust the situation of carrier injection and reduce the energy level barrier between the electrode and the electron transport layer. In addition, the Al in the middle layer will also be uniformly oxidized into Al2O3 in the air, and the naturally oxidized cathode has stronger air stability than the pure metal electrode with a low work function. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of the structure of the semi-transparent quantum dot electroluminescent device in the present invention;

[0026] Figure 2 It is a graph of current density, voltage and brightness (JVL) at the top and bottom of the semi-transparent quantum dot electroluminescent device provided in Comparative Example 1 of the present invention;

[0027] Figure 3 is a graph of current density, voltage and brightness (JVL) at the top and bottom of the semi-transparent quantum dot electroluminescent device provided in Example 1 of the present invention;

[0028] Figure 4 is a graph of current density, voltage and brightness (JVL) at the top and bottom of the semi-transparent quantum dot electroluminescent device provided in Example 2 of the present invention;

[0029] Figure 5 is a graph of current density, voltage and brightness (JVL) at the top and bottom of the semi-transparent quantum dot electroluminescent device provided in Example 3 of the present invention;

[0030] Figure 6 is a graph of current density, voltage and brightness (JVL) at the top and bottom of the semi-transparent quantum dot electroluminescent device provided in Example 4 of the present invention;

[0031] Figure 7 is a graph of current density, voltage and brightness (JVL) at the top and bottom of the semi-transparent quantum dot electroluminescent device provided in Example 5 of the present invention;

[0032] Figure 8 1 is a graph of transmittance-wavelength of the semi-transparent quantum dot electroluminescent device provided in Comparative Example 1, Example 1 and Example 2 of the present invention;

[0033] Fig. 9 is a transmittance-wavelength graph of the semi-transparent quantum dot electroluminescent device provided in Example 3, Example 4 and Example 5 of the present invention;

[0034] 1. Glass substrate; 2. ITO layer; 3. Hole transport layer; 4. Quantum dot layer; 5. Electron transport layer; 6. Cathode injection layer; 7. Ag cathode. DETAILED DESCRIPTION

[0035] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0036] In the description of the present invention, it should be noted that the orientations or positional relationships indicated by the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inside", "outside", etc. are based on the orientations or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention; the terms "first", "second", and "third" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance; in addition, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection or a detachable connection; it can be directly connected or indirectly connected through an intermediate medium, and it can be the internal communication of two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0037] The present invention provides a highly efficient semi-transparent quantum dot electroluminescent device for increasing the transmittance of a semi-transparent quantum dot electroluminescent device. The specific operation is to add an Al / Al2O3 layer of appropriate thickness. Since the work function of Al is lower than the work function of the selected electron transport layer, the injection barrier between the electron transport layer 5 and the semi-transparent electrode is eliminated, thereby improving the device carrier injection and further improving the overall performance of the device.

[0038] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a semi-transparent quantum dot electroluminescent device, which includes, from top to bottom, ITO conductive glass, a hole transport layer 3, a quantum dot layer 4, an electron transport layer 5, a cathode injection layer 6 and an Ag cathode layer 7, wherein the cathode injection layer is aluminum / aluminum oxide (Al / Al2O3), and the ITO conductive glass is composed of a glass substrate 1 and an ITO layer 2.

[0039] In some embodiments of the present invention, the hole transport layer 3 is one or more of TFB (poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine)), PEDOT:PSS (poly-3,4-ethylenedioxythiophene / polystyrene sulfonate) and TCTA (4,4',4"-tri(carbazole-9-yl)triphenylamine), and the thickness of the hole transport layer 3 is 30-45 nm.

[0040] Preferably, the hole transport layer 3 is a TCTA / TFB double-layer transport layer.

[0041] In some embodiments of the present invention, the quantum dot layer 4 is composed of inorganic cadmium selenide colloidal quantum dots, and the thickness of the quantum dot layer 4 is 25-30 nm. Cadmium selenide colloid refers to a colloid formed by cadmium selenide (CdSe) nanoparticles dispersed in a liquid medium (such as a solvent or a polymer), which has a quantum size effect.

[0042] In some embodiments of the present invention, the electron transport layer 5 is one of ZnO, ZnMgO, ZnAlO, and ZnZrO, and the thickness of the electron transport layer 5 is 25-30 nm.

[0043] As a preferred solution, the material of the electron transport layer 5 is any one of ZnMgO, ZnAlO or ZnZrO.

[0044] More preferably, the material of the electron transport layer 5 is ZnZrO.

[0045] In some embodiments of the present invention, the thickness of the aluminum / aluminum oxide cathode injection layer 6 is 1-4 nm. The thickness of the aluminum / aluminum oxide cathode injection layer will affect the transparency of the entire device, and preferably, the thickness is 2 nm.

[0046] In some embodiments of the present invention, the thickness of the Ag cathode layer 7 is 18-20 nm.

[0047] The second aspect of the present invention discloses a method for preparing a semi-transparent quantum dot electroluminescent device, characterized in that it comprises the following steps:

[0048] S1, obtaining an ITO conductive glass 1 as a substrate, pretreating it, and sequentially preparing a hole transport layer 3, a quantum dot layer 4, and an electron transport layer 5;

[0049] S2, preparing an aluminum / aluminum oxide (Al / Al2O3) cathode injection layer on the electron transport layer by vacuum evaporation;

[0050] S3, preparing and depositing a Ag cathode layer by vacuum evaporation method.

[0051] In some embodiments of the present invention, the process of S2 preparing a cathode injection layer on an electron transport layer is to use a process material with ITO conductive glass, a hole transport layer 3, a quantum dot layer 4 and an electron transport layer 5 as a substrate, place a mask on the substrate, weigh an appropriate amount of Al particles and put them into an Al evaporation boat, evacuate and heat for evaporation, open the substrate baffle to start evaporation, evaporate to a set thickness, and stop evaporation.

[0052] It should be noted that in S2, the Al layer is deposited by vacuum evaporation. After the evaporation, since the Al element is easily oxidized, a thin Al2O3 layer can be quickly formed on the upper surface of the Al layer.

[0053] In some embodiments of the present invention, the conditions for vacuum evaporation in S2 and S3 are: the vacuum degree is 1×10 -4 Pa, and the evaporation rate is 0.1 Å / s.

[0054] It should be understood that the preparation methods of the functional layers in the semi-transparent quantum dot electroluminescent device provided by the present invention are conventional in the art. For example:

[0055] The ITO conductive glass substrate can be obtained through commercial channels, and the pretreatment thereof includes: the ITO conductive glass substrate is sequentially cleaned by 40kHz ultrasonic wave for 15-30 minutes using at least one of detergent, water, deionized water, acetone and isopropyl alcohol. The cleaned ITO conductive glass is then dried in an oven at 100-150°C for 3-5 minutes, and then the ITO conductive glass substrate is treated with ultraviolet ozone (UVO) for 15-20 minutes.

[0056] Comparative Example 1

[0057] The present invention provides a semi-transparent quantum dot electroluminescent device, which comprises, from top to bottom, ITO conductive glass, a hole transport layer 3, a quantum dot layer 4, an electron transport layer 5 and an Ag cathode layer 7, and the specific preparation method thereof is as follows:

[0058] S1. Pretreatment and cleaning of ITO conductive glass. The ITO conductive glass was ultrasonically cleaned for 15 minutes using detergent, water, deionized water, acetone or isopropyl alcohol solvent respectively; then it was placed in a 150°C oven for drying for 15 minutes; finally, the substrate was placed in an ultraviolet ozone (UVO) machine for 15 minutes.

[0059] S2. Prepare a hole transport layer on the ITO conductive glass. The hole transport layer has two layers, namely, PEDOT:PSS layer and TFB:TCTA layer. Thaw the PEDOT:PSS solution and filter it through a 0.45 micron filter head, spin coat it at 3000 rpm for 35 seconds, and anneal it for 15 minutes to prepare the PEDOT:PSS layer; dissolve TFB:TCTA (3:1) in chlorobenzene solvent

[0060] S3, preparing a quantum dot layer on the hole transport layer, adding n-octane to the quantum dot solution (cadmium selenide solution) to dilute the solution concentration, and finally obtaining a 15 mg / mL quantum dot solution, and then spin coating the quantum dot solution, the parameters are: rotation speed 4000 rpm, time 35 s, and then annealing on a hot stage at 100° C. for 10 minutes. Thus, a quantum dot layer is prepared.

[0061] S4. Prepare an electron transport layer on the quantum dot layer. Prepare a 15 mg / mL ZnO ethanol solution, and prepare the electron transport layer by spin coating. The specific parameters are a spin coating speed of 4000 rpm and a time of 35 s. After spin coating, anneal on a hot plate at 100° C. for 10 minutes to obtain a ZnO electron transport layer.

[0062] S5. Prepare an Ag cathode layer on the electron transport layer. Place the substrate obtained in the previous step into a vacuum evaporator and evaporate a 20nm Ag cathode on the prepared quantum dot film. Specifically, place the substrate into the mask, weigh an appropriate amount of Ag particles and place them into the evaporation boat, and evacuate to 1×10 -4 Pa, heat and evaporate, maintain the rate at 0.1 angstrom / s, open the substrate baffle to start evaporation, and close the substrate baffle immediately after evaporation to 20nm.

[0063] Example 1

[0064] The present invention provides a semi-transparent quantum dot electroluminescent device, which comprises, from top to bottom, ITO conductive glass, a hole transport layer 3, a quantum dot layer 4, an electron transport layer 5, a cathode injection layer 6 and an Ag cathode layer 7. The specific preparation method is as follows:

[0065] S1. Pretreatment and cleaning of ITO conductive glass. The ITO conductive glass was ultrasonically cleaned for 15 minutes using detergent, water, deionized water, acetone or isopropyl alcohol solvent respectively; then it was placed in a 150°C oven for drying for 15 minutes; finally, the substrate was placed in an ultraviolet ozone (UVO) machine for 15 minutes.

[0066] S2. Deposit the hole transport layer on the ITO conductive glass. The hole transport layer has two layers, namely, the PEDOT:PSS layer and the TFB:TCTA layer. After the PEDOT:PSS solution is thawed and filtered through a 0.45 micron filter head, it is spin-coated at 3000 rpm for 35 seconds and annealed for 15 minutes to obtain a PEDOT:PSS layer with a thickness of 45 nm; TFB:TCTA (3:1) dissolved in chlorobenzene solvent is

[0067] S3. Prepare a quantum dot layer on the hole transport layer. Add n-octane to the quantum dot solution to dilute the solution concentration, and finally obtain a 15 mg / mL quantum dot solution, and then spin-coat the quantum dot solution with the following parameters: rotation speed 4000 rpm, time 35 s, and then anneal on a hot plate at 100°C for 10 minutes, thereby obtaining a quantum dot layer with a thickness of 30 nm.

[0068] S4. Prepare an electron transport layer on the quantum dot layer. Prepare a 15 mg / mL ZnO ethanol solution, and prepare an electron transport layer by spin coating. The specific parameters are a spin coating speed of 4000 rpm and a time of 35 s. After spin coating, anneal on a hot plate at 100° C. for 10 minutes to obtain a ZnO electron transport layer with a thickness of 30 nm.

[0069] S5. Prepare an Al / Al2O3 layer on the electron transport layer. Place the substrate obtained in the previous step into a vacuum coating machine and evaporate a 2nm Al / Al2O3 layer on the quantum dot layer. The specific operation is to place the substrate into the mask, weigh an appropriate amount of Al particles and place them into the Al evaporation boat, and evacuate to 1×10 -4 Pa, heat and evaporate, maintain the rate at 0.1 angstrom / s, open the substrate baffle to start evaporation, and immediately close the substrate baffle after evaporation to 2nm.

[0070] S6. Finally, prepare the Ag cathode layer on Al / Al2O3. Put the substrate obtained in the previous step into the vacuum evaporator, and evaporate 20nm of Ag cathode on the prepared Al / Al2O3 layer. The specific operation is to put the substrate into the mask, weigh an appropriate amount of Ag particles and put them into the evaporation boat, and evacuate to 1×10 -4 Pa, heat and evaporate, maintain the rate at 0.1 angstrom / s, open the substrate baffle to start evaporation, and close the substrate baffle immediately after evaporation to 20nm.

[0071] Example 2

[0072] This embodiment provides a semi-transparent quantum dot electroluminescent device. Compared with the embodiment 1, the difference is that the thickness of the Al / Al2O3 layer is different. The specific difference is:

[0073] The Al / Al2O3 layer is prepared on the quantum dot layer. The substrate obtained in step 4 of Example 1 is placed in a vacuum coating machine, and a 4nm Al / Al2O3 layer is evaporated on the quantum dot layer. The specific operation is to place the substrate in a mask, weigh an appropriate amount of Al particles and place them in an Al evaporation boat, and evacuate to 1×10 -4 Pa, heat and evaporate, maintain the rate at 0.1 angstrom / s, open the substrate baffle to start evaporation, and close the substrate baffle immediately after evaporation to 4nm.

[0074] Example 3

[0075] This embodiment provides a semi-transparent quantum dot electroluminescent device. Compared with Embodiment 1, the difference lies in that the material used for the electron transport layer is different. The specific difference is as follows:

[0076] A 15 mg / mL ZnZrO ethanol solution was prepared, and an electron transport layer was prepared by spin coating. The specific parameters were a spin coating speed of 4000 rpm and a time of 35 s. After spin coating, the solution was annealed on a hot plate at 100° C. for 10 minutes to obtain a ZnZrO electron transport layer with a thickness of 30 nm.

[0077] Example 4

[0078] This embodiment provides a semi-transparent quantum dot electroluminescent device. Compared with Embodiment 1, the difference lies in that the material of the electron transport layer is different. The specific difference is:

[0079] A 15 mg / mL ZnAlO ethanol solution was prepared, and an electron transport layer was prepared by spin coating. The specific parameters were a spin coating speed of 4000 rpm and a time of 35 s. After spin coating, the solution was annealed on a hot plate at 100°C for 10 minutes to obtain a ZnAlO electron transport layer with a thickness of about 30 nm.

[0080] Example 5

[0081] This embodiment provides a semi-transparent quantum dot electroluminescent device. Compared with Embodiment 1, the difference lies in that the material of the electron transport layer is different. The specific difference is:

[0082] A 15 mg / mL ZnMgO ethanol solution was prepared, and an electron transport layer was prepared by spin coating. The specific parameters were a spin coating speed of 4000 rpm and a time of 35 s. After spin coating, the solution was annealed on a hot plate at 100° C. for 10 minutes to obtain a ZnMgO electron transport layer with a thickness of about 30 nm.

[0083] Test performance

[0084] The semi-transparent quantum dot electroluminescent devices prepared in the examples and comparative examples of the present invention were subjected to optical and performance tests. The structural schematic diagrams of the various devices are shown in FIG. Figure 1 As shown, from bottom to top, there are glass substrate 1, ITO layer 2, hole transport layer 3 corresponding to each comparative example / embodiment, quantum dot layer 4, electron transport layer corresponding to each comparative example / embodiment, Al / Al2O3 layer and Ag cathode layer 7. Under the same conditions, bias voltage is applied to the comparative example and the embodiment to obtain the current density-bias voltage-luminous intensity curve of the bottom / top of the device as shown in Figures 2 to 7 When ZnO is used as the electron transport layer, the thickness of the Al / Al2O3 layer is changed, and the transmittance of the device is shown in Figure 8 As shown in Figure 2, when the thickness of the Al / Al2O3 layer is 2nm, the transmittance of the device at each wavelength is optimal. When the thickness of the Al / Al2O3 layer is 2nm, the electron transport layer is changed, and the corresponding transmittance of the device is as follows Fig. 9 As shown, when ZnZrO is used as the electron transport layer, the device transmittance is higher. The average transmittance (AVT) and device performance of the semi-transparent quantum dot electroluminescent device are shown in Table 1 below.

[0085] Table 1 Device efficiency

[0086]

[0087]

[0088] It can be concluded from the data in the table that the Al / Al2O3 layer plays an important role in the device performance and average transmittance of the semi-transparent quantum dot electroluminescent device. In the absence of the Al / Al2O3 layer, the performance of Comparative Example 1 is extremely low, and the maximum current efficiency at the top and bottom is only 11.5cd / A and 2.2cd / A, and the transmittance is extremely poor, only 31.65%. This is because the injection barrier between the Ag cathode and the electron transport layer is large, and a large amount of charge accumulates at the interface, which hinders the further injection of electrons, resulting in poor performance of Comparative Example 1. The Al / Al2O3 layer has a lower work function (3.5eV), which is less than the Fermi level of the adjacent electron transport layer (~3.87eV), which allows the two to form an ohmic contact to eliminate the injection barrier between the cathode and the electron transport layer, reduce energy loss, and thus effectively improve the overall efficiency of the device. By introducing the Al / Al2O3 layer, the start-up voltage of Comparative Example 1 and Comparative Example 2 is significantly reduced, indicating that the energy consumption of injected electrons is reduced. In Example 3, Example 4 and Example 5, ZnO is doped with Zr, Al and Mg to change the carrier mobility of the electron transport layer to match the hole injection on the anode side, so that the carrier injection of the device under the bias voltage is more balanced to achieve efficient emission. Among them, the brightness of the semi-transparent quantum dot electroluminescent device with ZnZrO as the electron transport layer reached 387506cd / m 2 (bottom) and 63751cd / m 2 (Top), the maximum current efficiency of the bottom and top emission is 52.4cd / A and 6.2cd / A respectively, and the bottom / top brightness ratio reaches 6.1:1, which shows the high luminous efficiency of Example 3. Example 4 and Example 5 use two electron transport layers, ZnAlO and ZnMgO, respectively. The efficiency of the two devices is lower than that of Example 3, which shows that the electron injection rate of ZnAlO and ZnMgO is unbalanced with the hole injection, and the excessive accumulation of electrons / holes leads to the decrease of device efficiency.

[0089] The average light transmittances of Examples 3, 4 and 5 are close.

[0090] In the above embodiment, ZnO is doped with other elements, which changes the ZnO energy band position and reduces the electron injection density. When doped with Zr, ZnZrO has a more suitable energy level and a suitable electron injection density, so that the device has the highest efficiency.

[0091] Example 6

[0092] This embodiment provides a semi-transparent quantum dot electroluminescent device. Compared with the embodiment 1, the difference is that the thickness of the Al / Al2O3 layer is different. The specific difference is:

[0093] The Al / Al2O3 layer is prepared on the quantum dot layer. The substrate obtained in step 4 of Example 1 is placed in a vacuum coating machine, and a 4nm Al / Al2O3 layer is evaporated on the quantum dot layer. The specific operation is to place the substrate in a mask, weigh an appropriate amount of Al particles and place them in an Al evaporation boat, and evacuate to 1×10 -4 Pa, heat and evaporate, maintain the rate at 0.1 angstrom / s, open the substrate baffle to start evaporation, and immediately close the substrate baffle after evaporation to 1nm.

[0094] Example 7

[0095] This embodiment provides a semi-transparent quantum dot electroluminescent device. Compared with Embodiment 1, the difference is that the material of the hole transport layer 3 used in this embodiment is TFB.

[0096] Example 8

[0097] This embodiment provides a semi-transparent quantum dot electroluminescent device. Compared with Embodiment 1, the difference is that the material of the hole transport layer 3 used in this embodiment is TCTA.

[0098] Example 9

[0099] This embodiment provides a semi-transparent quantum dot electroluminescent device. Compared with Embodiment 1, the difference is that the thickness of some structural layers is: the thickness of the hole transport layer 3 is 30nm, the thickness of the quantum dot layer 4 is 25nm, the thickness of the electron transport layer 5 is 25nm, and the thickness of the Ag cathode layer 7 is 18nm.

[0100] Example 10

[0101] This embodiment provides a semi-transparent quantum dot electroluminescent device. Compared with Example 1, the difference is that the thickness of some structural layers is: the thickness of the hole transport layer 3 is 40nm, the thickness of the quantum dot layer 4 is 28nm, the thickness of the electron transport layer 5 is 28nm, and the thickness of the Ag cathode layer 7 is 19nm.

[0102] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made on the basis of the above. It is not necessary and impossible to list all implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.

Claims

1. A semi-transparent quantum dot electroluminescent device, characterized in that: It comprises a glass substrate (1), an ITO layer (2), a hole transport layer (3), a quantum dot layer (4), an electron transport layer (5), a cathode injection layer (6) and an Ag cathode layer (7) which are arranged in sequence from bottom to top; The cathode injection layer (6) is a composite layer of aluminum and aluminum oxide, with the aluminum oxide being on the upper side of the aluminum.

2. A semi-transparent quantum dot electroluminescent device according to claim 1, characterized in that: The hole transport layer (3) is any one or more of TFB, PEDOT:PSS and TCTA.

3. A semi-transparent quantum dot electroluminescent device according to claim 1, characterized in that: The quantum dot layer (4) is cadmium selenide colloid.

4. A semi-transparent quantum dot electroluminescent device according to claim 1, characterized in that: The electron transport layer (5) is any one of ZnO, ZnMgO, ZnAlO and ZnZrO.

5. A semi-transparent quantum dot electroluminescent device according to claim 1, characterized in that: The thickness of the cathode injection layer (6) is 1-4 nm.

6. A semi-transparent quantum dot electroluminescent device according to claim 1, characterized in that: The thickness of the hole introduction layer (3) is 30-45 nm; the thickness of the quantum dot layer (4) is 25-30 nm.

7. A semi-transparent quantum dot electroluminescent device according to claim 1, characterized in that: The thickness of the electron transport layer (5) is 25-30 nm, and the thickness of the Ag cathode layer (7) is 18-20 nm.

8. A method for preparing the semi-transparent quantum dot electroluminescent device according to claim 1, characterized in that: The following steps are involved: S1, sequentially preparing a hole transport layer (3), a quantum dot layer (4) and an electron transport layer (5) on the ITO layer (2); S2, preparing a cathode injection layer (6) on the electron transport layer (5) by vacuum evaporation; S3, depositing a Ag cathode layer (7) on the cathode injection layer (6).

9. The method for preparing a semi-transparent quantum dot electroluminescent device according to claim 8, characterized in that: In S2, the process of preparing the cathode injection layer (6) by vacuum evaporation is as follows: A substrate comprising a glass substrate (1), an ITO layer (2), a hole transport layer (3), a quantum dot layer (4) and an electron transport layer (5) is placed in an evaporation chamber, a mask is placed on the electron transport layer (5), Al particles are placed in an evaporation boat, vacuum is drawn and heated for evaporation, an Al layer is evaporated on the electron transport layer (5) as a cathode injection layer (6), and the evaporation is stopped after the evaporation reaches a set thickness.

10. The method for preparing a semi-transparent quantum dot electroluminescent device according to claim 9, characterized in that: During the vacuum deposition process, the vacuum degree is 1×10 -4 Pa, and the evaporation rate is 0.1 Å / s.